Penerapan Teknologi Informasi (TI) dalam Dunia Pendidikan (Kajian Manajemen Software Perpustakaan) - Nasrul Makdis (Universitas Islam Negeri Imam Bonjol Padang, 2018)
The application of Information Technology (IT) has now spread in almost all fields including in the field of libraries. The library as an information management institution is one of the fields of rapid application of information technology. The size of the development of many types of libraries is measured from the application of information technology that is used and not from other size scales such as the size of the building used, the number of collections available and the number of users. The need for IT is closely related to the role of libraries as a force in the preservation and dissemination of information on science and culture that develops along with writing, printing, educating and the human need for information. The application of information technology in the library can be used in two forms. First, the application of information technology is used as a Library Management Information System. Second, the application of information technology as a means to store, obtain and disseminate scientific information in digital format. Both functions of the application of information technology can be separate or integrated, depending on an information system and the ability of the software used. This paper tries to see how the application and management of library software is implemented.